A long non-coding RNA lncRNA18313 regulates resistance against cadmium stress in wheat - Zhao, Sujing; Bai, Hongxia; Fan, Ziyi; Zhu, Mo; Qiu, Zongbo (Frontiers in Plant Science, 2025)
Long non-coding RNAs (lncRNAs) have been demonstrated to play key roles in plant response and adaptation to heavy metal stresses. However, the exact biological functions and potential regulatory mechanism, especially in wheat’s response to cadmium (Cd) stress, are still poorly understood. We have previously discovered a Cd stress-related lncRNA in wheat, namely TalncRNA18313. In this study, qRT-PCR analysis revealed that TalncRNA18313 was expressed extensively in wheat leaves, and its accumulation was highly induced by Cd stress. To further fully explore the function of lncRNA18313 in response to Cd stress, lncRNA18313 was cloned from wheat (Triticum aestivum L.), and was transformed into Arabidopsis. When TalncRNA18313 was heterologous expressed in Arabidopsis, the transgenic plants exhibited enhanced Cd tolerance characterized by lower malondialdehyde (MDA) levels and higher activities of key antioxidant enzymes, such as catalase (CAT), superoxide dismutase (SOD) and peroxidase (POD). Subsequently, RNA-sequencing (RNA-seq) analysis demonstrated that 370 genes were differentially expressed in lncRNA18313 overexpressing transgenic lines under Cd stress comparing to wild type plants. Among the genes regulated by lncRNA18313, the most significantly enriched were those involved in transcriptional regulation and antioxidative defense responses. These results suggest that TalncRNA18313 plays a crucial role in improving Cd tolerance in wheat by modulating key stress-related pathways, particularly those critical for coping with oxidative damage and regulating gene expression under Cd stress. This discovery contributes to the expanding understanding of knowledge about the involvement of lncRNAs in plant stress responses and offers promising potential for improving crop resilience to environmental stresses.